Training of trainers technical and gender transformative interventions with the Kolping Society of Tanzania - Mwakanyamale, D.F.; Msita, S.; Cole, Steven; Richius, K.; Witness, F.; Wivina, L.; Dennis, M. (International Institute of Tropical Agriculture, 2025)
The Gender Equality Initiative generated evidence on restrictive gender norms within the cassava agrifood system in northwestern Tanzania and identified key leverage points and levers through stakeholder consultations. Building on these findings, the International Institute of Tropical Agriculture (IITA) collaborated with the Kolping Society of Tanzania (KST) to co-design Gender Transformative (GT) interventions aimed at addressing these normative constraints in Kagera Region. The interventions specifically target restrictive norms that limit women working in the cassava agrifood system from owning agricultural land and making key decisions, including those related to loans and major household expenditures. These GT interventions were designed to be piloted alongside cassava-based technical interventions that KST are already implementing as part of their ongoing programs. To support the rollout, guides and manuals were developed to assist facilitators in implementing the interventions within farmer organizations.